Study of oxidized low density lipoprotein and augmentation index among population - Nazir, Mohd Hakam; Aung, Nilar; Abdullah, Nor Zamzila; Samsuddin, Niza (2013)

(untitled)
Arterial stiffness is defined as the hardening of the arteries due to loss of their elastic properties. Stiffening of arterial wall can be a good biomarker for increased cardiovascular disease thus measuring arterial stiffness is recommended in the preventive management of cardiovascular disease. Arterial stiffness is also associated with a number of cardiovascular disease risk factors like age, smoking, gender, hypertension, obesity, hypercholesterolemia and diabetes. The aim of this research is to study the ox-LDL and augmentation index (AIx) among apparently healthy subjects in ‘Chengal Lempong’ village together with their associations. The subjects (n=85) of age (>18 years) were randomly selected as participants in the study. A sandwich enzyme-linked immunoadsorbent assay (ELISA) was used to measure ox-LDL. The augmentation index (AIx) which reflects the arterial stiffness was determined by using non-invasive applanation tonometry, Sphygmo Cor. The current study showed that mean of the age was 40±8 years with male and female distribution of 38(45%) and 47(55%) respectively. 35.3% of the subjects were obese and 41.2% were overweight. 23 (28%) of them were smoker. There was a significant positive correlation between age and ox-LDL (r = 0.4, p <0.05). AIx was positively correlated with gender (p< 0.05) and smoking (p< 0.05). There was a positive correlation between ox- LDL and AIx ( r = 0.2 at p= 0.05) . The present study found that a higher ox-LDL was related with increased AIx. This showed that the increased arterial stiffness suggesting that oxidative modification of oxidized LDL may affect in the alteration of arterial wall elastic properties.